Ethnophysics Edutainment: Exploring the Potential of Local Wisdom-Based Virtual Reality Media Development in Physics Education - Mozza Pinkan Edelweiss; Yuhanes Hari Nugroho; Julianto Julianto; Nina Fajriyah Citra; Utama Alan Deta (Reog: Journal of Ecoethnoscience Education, 2026)
Physics education is often perceived as abstract and lacking context, leading to low interest and engagement among students. The integration of local wisdom and immersive technologies, such as Virtual Reality (VR), is seen as a promising approach to bridging this gap. This study aims to explore the needs of students in the development of VR-edutainment media based on ethnophysics as an alternative to traditional physics learning, which is more contextual, interactive, and meaningful. The study employs a quantitative descriptive approach using simple random sampling techniques with 30 high school students, comprising grades X and XI. The instrument was an online questionnaire comprising 20 statements grouped into four main aspects: interest in learning physics, integration of local wisdom, science literacy, and technology utilization. The collected data were analyzed using descriptive statistics to identify trends in student responses, supplemented by qualitative interpretations to enhance the understanding of the findings. The results showed that the majority of students responded positively to physics learning linked to local wisdom, while also showing high enthusiasm for the use of interactive technology. More than 80% of respondents stated that digital simulations helped them understand concepts and made learning more enjoyable; however, a small number of students still struggled to explain natural phenomena scientifically. These findings underscore the importance of learning media that integrates local culture with immersive technology, thereby enhancing the learning experience to be more contextual, meaningful, and aligned with the needs of the digital generation. In conclusion, this study successfully mapped the initial needs of students for the development of ethnophysics-based VR edutainment media. The development of ethnophysics-based VR-edutainment media holds significant potential to enhance science literacy while strengthening students’ connection to their cultural heritage, thereby fostering more meaningful and transformative learning experiences.